The Effect of Fastener Type (Clamex P14 and Tenso P14) and Adhesive Type on Compression and Tension Performance - Karaman, Abdurrahman (Bartın Üniversitesi, 2020)
In this study, the effects of different fasteners (Clamex P14 and Tenso P14) for medium density fiberboard (MDFLamM) surfaced with synthetic resin sheet wood-based materials as well as several adhesives (PVAc-D4) and PU-D4) on diagonal tension and compression forces, were analysed. In the study, melamine coated medium density fiberboard (MDF-Lam) was used as wood-based material, Clamex P14 and Tenso P14 were used as fasteners and polyvinylacetate (PVAc-D4) and polyurethane (PU-D4) glues were used as adhesive agents. The diagonal tension and compression force tests were applied on 120 pieces of test samples prepared in this respect based on the principles of ASTM D 1037. As a result, The diagonal compression and tensile forces values were found in the highest Clamex P14 fastener and polyvinylacetate adhesive bond (PVAc-D4), the lowest was in the joint with Tenso P14 fastener without any adhesive agent. For L type corner-joints, it is suggested to use Clamex P14 as a fastener and polyvinylacetate adhesive (PVAc-D4) as the type of the adhesive agent.

Bu çalışmada, ahşap esaslı malzemelerden (MDFLam) levhada farklı bağlantı elemanları (Clamex P14 ve Tenso P14) ve çeşitli tutkalların (PVAc-D4 ve Pu-D4) diyagonal basma ve çekme kuvvetine etkileri araştırılmıştır. Çalışmada ahşap esaslı malzeme olarak melamin plaka ile kaplanmış orta yoğunlukta lif levha (MDF Lam), bağlantı elemanı olarak Clamex P14 ve Tenso P14, yapıştırıcı olarak ise polivinilasetat (PVAc-D4) ve poliüretan (PU-D4) tutkalları kullanılmıştır. Hazırlanan 120 adet deney örneğine ASTM D 1037 esaslarına göre diyagonal basma ve çekme deneyi uygulanmıştır. Sonuç olarak, diyagonal basma kuvveti, en yüksek Clamex P14 bağlantı elemanlı polivinilasetat tutkallı (PVAc-D4) birleştirmede (96.97 N), en düşük; Tenso P14 bağlantı elemanlı tutkalsız birleştirmede (Kontrol) (68.69 N) bulunmuştur. Diyagonal çekmede; Clamex P14 bağlantı elemanlı polivinilasetat tutkallı (PVAc-D4) birleştirmede (206.90 N), en düşük ise Tenso P14 bağlantı elemanlı tutkalsız birleştirmede (Kontrol) (168.80 N) çıkmıştır. L tipi köşe birleştirmelerinde bağlantı elemanı olarak Clamex P14 ile tutkal tipi olarak ise polivinilasetat (PVAc-D4) tutkalının kullanılması önerilebilir.
Bağlantı Elemanı Tipi (Clamex P14 ve Tenso P14) ve Tutkal Çeşidinin Diyagonal Çekme ve Diyagonal Basma Kuvvetine Etkileri
Keywords: Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler